Forskolin Editing via Radical Iodo- and Hydroalkylation - Pruteanu, Elena; Tappin, Nicholas D. C.; Gîrbu, Vladilena; Morarescu, Olga; Dénès, Fabrice; Kulciţki, Veaceslav; Renaud, Philippe (Synthesis, 2021)
The modification of highly oxygenated forskolin as well as manoyl and epi-manoyl oxide, two less functionalized model substrates sharing the same polycyclic skeleton, via intermolecular carbon-centered radical addition to the vinyl moiety has been investigated. Highly regio- and reasonably stereoselective iodine atom transfer radical addition (ATRA) reactions were developed. Unprotected forskolin afforded an unexpected cyclic ether derivative. Protection of the 1,3-diol as an acetonide led the formation of the iodine ATRA product. Interestingly, by changing the mode of initiation of the radical process, in situ protection of the forskolin 1,3-diol moiety as a cyclic boronic ester took place during the iodine ATRA process without disruption of the radical chain process. This very mild radical-mediated in situ protection of 1,3-diol is expected to be of interest for a broad range of radical and non-radical transformations. Finally, by using our recently developed tert-butylcatechol-mediated hydroalkylation procedure, highly efficient preparation of forskolin derivatives bearing an extra ester or sulfone group was achieved.
Keywords: radical reaction; natural product modification; alkenes; boronic ester; 1,3-diol protecting group; triethylborane